2021
DOI: 10.3389/fpsyt.2021.704631
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity of the Nucleus Accumbens Network Between Deficit and Non-deficit Schizophrenia

Abstract: Deficit schizophrenia (DS), which is marked by stable negative symptoms, is regarded as a homogeneous subgroup of schizophrenia. While DS patients have structurally altered nucleus accumbens (NAcc) compared to non-deficit schizophrenia (NDS) patients and healthy individuals, the investigation of NAcc functional connectivity (FC) with negative symptoms and neurocognition could provide insights into the pathophysiology of schizophrenia. 58 DS, 93 NDS, and 113 healthy controls (HCs) underwent resting-state functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The activation of NAcc is associated with the vividness of hallucinations ( 33 ) and auditory verbal imagery in schizophrenia patients ( 34 ). Moreover, the abnormal FC ( 20 , 35 ) and gray matter changes ( 36 ) of NAcc appeared to be associated with the presence of AVH and neurocognitive impairments. The results may indicate the unique role of NAcc in investigating the neural mechanisms of schizophrenia with AVH.…”
Section: Introductionmentioning
confidence: 95%
“…The activation of NAcc is associated with the vividness of hallucinations ( 33 ) and auditory verbal imagery in schizophrenia patients ( 34 ). Moreover, the abnormal FC ( 20 , 35 ) and gray matter changes ( 36 ) of NAcc appeared to be associated with the presence of AVH and neurocognitive impairments. The results may indicate the unique role of NAcc in investigating the neural mechanisms of schizophrenia with AVH.…”
Section: Introductionmentioning
confidence: 95%
“…DS and NDS patients were diagnosed according to the Chinese version of the Schedule for the Deficit Syndrome (SDS) [ 34 ]. The inclusion and exclusion criteria used to choose the subjects are presented in our previously published studies [ 19 , 22 , 35 ] and are provided in the SI Methods . All participants provided written informed consent, which was approved by the Institutional Ethical Committee for Clinical Research of the Affiliated Brain Hospital of Nanjing Medical University and ZhongDa Hospital Affiliated to Southeast University.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous neuroimaging studies have identified brain function alterations associated with cognitive impairments, symptom severity, and treatment effects in patients with SCZ [ 14 18 ]. Similarly, studies on DS have reported distinct abnormal functional changes compared to NDS [ 19 ], particularly in brain networks such as the default mode network [ 20 ], salience network [ 21 ], and nucleus accumbens network [ 22 ]. Many of these studies have also demonstrated specific associations between alterations in functional connectivity (FC) and negative symptoms and cognitive impairments in DS.…”
Section: Introductionmentioning
confidence: 99%
“… Zhou et al (2019a) probed numerous abnormal FCs of nerve pathways between the two patient groups, mainly concentrated in the frontooccipital, frontotemporal, and insula-visual cortex, as well as the temporooccipital pathway. In addition, a recent study demonstrated abnormal patterns of FC in the nucleus accumbens network between DS and NDS ( Zhou et al, 2021 ). Meanwhile, using the independent component analysis (ICA) method, further studies found the modular-level alterations in DS compared with the NDS and healthy controls, and the distinct and common disruptions mainly focus on SN, sensory motor network (SMN), DMN, and VN ( Yu et al, 2017 ; Zhou et al, 2019b ; Fan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%